Fire and Brimstone: Molecular Interactions between Sulfur and Glucosinolate Biosynthesis in Model and Crop Brassicaceae - Borpatragohain, Priyakshee; Rose, Terry J.; King, Graham J. (Frontiers in Plant Science, 2016)
Glucosinolates (GSLs) represent one of the most widely studied classes of plant secondary metabolite, and have a wide range of biological activities. Their unique properties also affect livestock and human health, and have been harnessed for food and other end-uses. Since GSLs are sulfur (S)-rich there are many lines of evidence suggesting that plant S status plays a key role in determining plant GSL content. However, there is still a need to establish a detailed knowledge of the distribution and remobilization of S and GSLs throughout the development of brassica crops, and to represent this in terms of primary and secondary sources and sinks. The increased genome complexity, gene duplication and divergence within brassicas, together with their ontogenetic plasticity during crop development, appear to have a marked effect on the regulation of S and GSLs. Here we review the current understanding of inorganic S (sulfate) assimilation into organic S forms, including GSLs and their precursors, the intracellular and inter-organ transport of inorganic and organic S forms, and the accumulation of GSLs in specific tissues. We present this in the context of overlapping sources and sinks, transport processes, signaling molecules and their associated molecular interactions. Our analysis builds on recent insights into the molecular regulation of sulfate uptake and transport by different transporters, transcription factors (TF) and miRNAs, and the role that these may play in GSL biosynthesis. We develop a provisional model describing the key processes that could be targeted in crop breeding programs focused on modifying GSL content.